Amino acids, polyols and soluble fibres as sugar replacers in bakery applications: Egg white proteins denaturation controlled by hydrogen bond density of solutions. (November 2020) - Renzetti, Stefano; van den Hoek, Irene A.F.; van der Sman, Ruud G.M.
Abstract: In this paper we demonstrate that the denaturation behavior, i.e. T den, of egg white proteins in sugar and sugar replacer solutions is explained by the volumetric density of hydrogen bonds in the solutions, i.e. n O H, e f f . The validity of the presented approach is demonstrated using 18 solutions comprising single compounds as well as 7 ternary/quaternary mixtures. Different classes of plasticizers are used at various concentrations and at various ratio with proteins. Sweet amino acids such as l -proline and glycine are included as novel alternatives to polyols. The experimental data are modelled with the Flory-Huggins (FH) theory for biopolymer melting. For such purpose, solutions are treated as a single solvent, which is described by the effective volume fraction of the solvent Φ w, e f f (⁓ n O H, e f f ). Overall, the FH model can well describe the denaturation behavior of egg white proteins in sugar and sugar replacer solutions up to 30% concentration. Deviations from the model become particularly evident at high sugar concentrations (i.e. 50%), which relate to conditions of phase separation in a protein-rich and sugar-rich domain. In such conditions, Φ w, e f f does not reflect the composition of the solvent around the proteins. An elevation in T den is observed due to a reduction in hydrogen bond density in the protein-rich domain. The results indicate that phase separation is driven by both the concentration and the molar volume density of effective hydroxyl groups N OH, s /v s of the plasticizers or plasticizer mixtures. Finally, the proposed approach can predict key phase-transitions which result in protein network formation in pound cake baking. Graphical abstract: Image 1 Highlights: Hydrogen bond density in sugar solutions determines egg white protein denaturation. Denaturation is predicted with Flory-Huggins extended for hydrogen bond density. Phase separation results in deviation from model predictions. Phase separation occurs depending on plasticizer type and concentration. Model predicts key phase-transitions for protein network formation in cake baking.